2014
DOI: 10.2174/1874120701408010001
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Model for the Evaluation of the Magnetic Stimulation of Peripheral Nerves

Abstract: In this paper, a numerical procedure for the analysis of peripheral nerve excitation through magnetic stimulation is presented and used to investigate the physical parameters influencing stimulation. The finite difference technique is used to evaluate the electric field distribution induced inside an arm by the current flowing through a coil, and a nonlinear cable model is used to describe the response of the nerve fiber to the induced electric field. The comparison among several forearm structures has evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In work toward a more predictive model of the field/body/nerve interactions, simulations have been recently performed to assess the interaction between the electric field and the nerve to inform nerve response (31, 32, 33, 28, 34, 35, 36, 37). These investigations were begun as simplified straight nerve segments placed in small body models (approximately 10 cm) to evaluate the effect of the electric field on the neurodynamics and extended by Neufeld and colleagues to study segments of the ulnar and sciatic nerves within a detailed body model (38, 39).…”
Section: Introductionmentioning
confidence: 99%
“…In work toward a more predictive model of the field/body/nerve interactions, simulations have been recently performed to assess the interaction between the electric field and the nerve to inform nerve response (31, 32, 33, 28, 34, 35, 36, 37). These investigations were begun as simplified straight nerve segments placed in small body models (approximately 10 cm) to evaluate the effect of the electric field on the neurodynamics and extended by Neufeld and colleagues to study segments of the ulnar and sciatic nerves within a detailed body model (38, 39).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the nerve tissue and surrounding tissue is another issue which needs to be addressed. Results from Pisa et al (2014). found that the best trade-off between accuracy and computational expense was achieved by modeling surrounding tissue using an anatomically correct model with heterogeneous but non-dispersive tissue characteristics.…”
Section: Nerve Modelmentioning
confidence: 99%
“…The analysis domain is divided into homogeneous cells (Δ × Δ × Δ ) centered at the point of coordinates ( , , ) in a Cartesian grid that can be represented as a network of lumped electrical elements (see Figure 2 of [45] for a simplified 2D representation) [45,49,50].…”
Section: Calculation Of the Induced ⃗ Fieldmentioning
confidence: 99%